MODIFIKASI MEJA PACKING DENGAN METODE REVERSE ENGINEERING DAN VDI 2221 - Delfieco, Anggata; Daywin, Frans Jusuf; Adianto (Jurnal Mitra Teknik Industri, 2023)
Productivity improvement can be done for the success of MSMEs, but MSMEs in Indonesia are experiencing obstacles, especially in tools in production activities that are not well organized and work that is uncomfortable when carrying out work processes. This research was conducted at UMKM DWI VARISI located in Jatiuwung, Gembor. UMKM DWI VARIASI sells different types of car exteriors that are sold through several available e-commerce sites. The purpose of this study is to identify the causes of productivity disruptions, where the research calculates the standard time, identifies complaints and analyzes work posture, designs powerful work aids, and provides suggestions for improvements to improve worker comfort. Before compounding the packing table at UMKM DWI VARIASI were carried out packing table analysis with reverse engineering for packing table parts, with the VDI 2221 design method. Meanwhile, to determine the standard time, use a stopwatch time study for the packing process and ergonomic methods to determine the complaints felt by workers. The ergonomic method used to determine complaints was used by the Nordic Body Map, and REBA questionnaires.